El lugar de la sociología en las ONG y en la enseñanza universitaria. Un dilema no resuelto. Reflexiones y propuestas - Vargas Morales, Zenón Eduardo (2006)
There are no doubts that the fundamental perspective in the university education of sociology at the present moments are more and more complex by the great transforming force of the globalización and the modernization in the today world. Fact that it demands to that we cultivated sociology, new epistemológicas, theoretical and methodologic reflections from a interdisciplinary perspective. In that measurement, which I try is only to sketch some ideas on the university education of sociology, having to San main Marcos like my referring of observation and reflection. Also, those have been my students that have motivated me to these preoccupations when observing in them every time a greater interest by classic the questions practical and instrumental before the knowledge of and the contemporary ones of sociology and rethink sociological with them on the complex social, political and cultural plot of the country. It seemed important to me to make these notes, directed mainly to them.